Polylactic acid: synthesis and biomedical applications - Singhvi, M. S.; Zinjarde, S. S.; Gokhale, D. V. (Journal of Applied Microbiology, 2019)
Social and economic development has driven considerable scientific and engineering efforts on the discovery, development and utilization of polymers. Polylactic acid (PLA) is one of the most promising biopolymers as it can be produced from nontoxic renewable feedstock. PLA has emerged as an important polymeric material for biomedical applications on account of its properties such as biocompatibility, biodegradability, mechanical strength and process ability. Lactic acid (LA) can be obtained by fermentation of sugars derived from renewable resources such as corn and sugarcane. PLA is thus an eco-friendly nontoxic polymer with features that permit use in the human body. Although PLA has a wide spectrum of applications, there are certain limitations such as slow degradation rate, hydrophobicity and low impact toughness associated with its use. Blending PLA with other polymers offers convenient options to improve associated properties or to generate novel PLA polymers/blends for target applications. A variety of PLA blends have been explored for various biomedical applications such as drug delivery, implants, sutures and tissue engineering. PLA and their copolymers are becoming widely used in tissue engineering for function restoration of impaired tissues due to their excellent biocompatibility and mechanical properties. The relationship between PLA material properties, manufacturing processes and development of products with desirable characteristics is described in this article. LA production, PLA synthesis and their applications in the biomedical field are also discussed.
Keywords: Biocompatible; biodegradable; drug delivery; implants; l- and d-lactic acid; polylactic acid